Pattern of serum lipid profile of type 2 diabetes patients in a tertiary hospital in Nigeria - Reng, Rifkatu S.; Onwuegbuzie, Gerald A.; Anumah, Felicia (International Journal of Research in Medical Sciences, 2021)
Background: Diabetes mellitus is a metabolic disorder characterised by chronic hyperglycemia and disturbances of carbohydrate, lipid and protein metabolism. Diabetic patients have an increased risk of developing dyslipidemia with various lipid abnormalities which makes them prone to develop cardiovascular disease. The aim of the study is to determine the patterns of lipid profile in patients with Type 2 diabetes mellitus. Methods: Lipid profile data for a total of 104 known type 2 DM patients from the medical outpatient clinic were collected. The profile of the study sample was analysed for dyslipidemia using the ATP III classification. Data obtained were analysed using Analyse-it v3.0 statistical software for Microsoft Excel. Results: This study showed that there were more females 53.8% than males 46.2% with type 2 diabetes mellitus with the mean age of 52.5±11.9 years. The pattern of dyslipidaemia revealed elevated LDL 51.9%, TG 37.5%, TC 36.5% and low HDL 27.9%. We had more patients who were overweight 33.7% than obese 32.7%. Conclusions: It was observed from the study that a significant number of diabetic patients have dyslipidaemia and most common lipid abnormalities are elevated LDL, triglyceride and low HDL.